Effectiveness of a short-term oxygen therapy training program in Liberia during and after COVID-19 - Luke, Mark B.; Ziah, Moses; Lu, Lily Zhi Ning; Davis, Michael D.; Arzoaquoi, Samson; Drucker, Eva; Kanneh, Foday; Logan, Gorbee G.; Massaquoi, Moses (Frontiers in Public Health, 2025)
BackgroundAccess to high-quality medical oxygen has been a long-standing challenge in Liberia due to barriers that span across the health system, which were amplified during the COVID-19 pandemic. The surge in cases requiring oxygen therapy necessitated rapid capacity-building for healthcare workers. In response, an emergency oxygen training package was adapted and implemented by the Liberia Ministry of Health and the National Incidence Management System. This manuscript evaluates the implementation of a short-term respiratory care training package to rapidly build healthcare worker capacity during the COVID-19 response and its adaptation for routine in-service training post-response.MethodsThe emergency training used the “hot and cold” simulation approach from the 2014 Ebola response, consisting of a cold phase (3-days) with didactic lectures and practical sessions, and mock COVID treatment unit simulations (2-days); and a hot phase within an active CTU. Participants were doctors, physician assistants, nurses, or midwives, deployed to COVID treatment units at major health centers and hospitals across all counties in Liberia. Training assessments consisted of a paper-based knowledge test pre- and post-training, and Objective Structured Clinical Examinations post-training.ResultsThe emergency training as part of COVID response included 123 health care workers from 43 health facilities and saw a significant increase in knowledge (median score of 46% pre-training vs. 84% post-training, p < 0.001). Adaptation and piloting of the package for routine in-service training was also effective at increasing knowledge amongst 81 health care workers (median score of 41% pre-training vs. 78% post-training, p < 0.001). High post-training Objective Structured Clinical Examination scores demonstrated clinical competency achievement in both cohorts. For emergency training, median scores were 92% (pulse oximetry), 81% (oxygen cylinders), and 83% (oxygen concentrators). For routine in-service training, scores were 88, 82, and 84%, respectively.ConclusionWe demonstrate that the implementation of a healthcare worker training package in oxygen therapy during the COVID response in Liberia and its eventual integration into a routine in-service training program was able to achieve significant improvements in health care worker knowledge and skills. This highlights the feasibility of using rapid and short-term training to enhance clinical capacity within both emergency and post-response settings in a resource-limited country.